Detection and phylogenetic analysis of Dabieshan tick virus and Okutama tick virus in ticks collected from Cape Toi, Japan - Hirohisa Mekata; Ikuo Kobayashi; Tamaki Okabayashi (Ticks and Tick-Borne Diseases, 2023)
New technologies have led to the discovery of novel tick-borne and tick-associated viruses. Dabieshan tick virus (DaTV) and Okutama tick virus (OkTV), which belong to the family Phenuiviridae, were discovered in ticks in China and Japan, respectively, in the 2010s. Although it is unknown whether these viruses cause disease in animals or humans, all tick-associated viruses have the potential to become etiological agents of infectious diseases through gene reassortment. Therefore, it is important to elucidate the ecology of these viruses, regardless of their pathogenicity. In this study, ticks were collected year-round in Cape Toi, Miyazaki Prefecture, Japan, and an epidemiological survey of tick-associated phenuiviruses was performed. A total of 516 ticks collected from the vegetation by dragging flannel sheets were used for analysis. Pan-phenuivirus reverse transcription PCR was performed on the tick samples, and DaTV and OkTV were detected. We found that 37.0% (85/230) and 23% (16/71) of nymphal and adult Haemaphysalis longicornis were infected with DaTV, respectively, and 10% (6/62) and 13% (1/8) of nymphal and adult Haemaphysalis flava were infected with OkTV, respectively. Phylogenetic analysis indicated that the DaTV identified in this study formed a unique clade that was distinct from the strains identified in China. The survey revealed that DaTV is distributed not only in China, but also in Japan. We believe that this study contributes to our understanding of the prevalence of tick-associated viruses.